Effects of Zinc Gluconate and 2 Other Divalent Cationic Compounds on Olfactory Function in Mice - Duncan-Lewis, Christopher A (American Association for Laboratory Animal Science, 2011)
Intranasal application of zinc gluconate has commonly been used to treat the common cold. The safety of this treatment, however, has come into question recently. In addition to a United States recall of a homeopathic product that contains zinc gluconate, abundant literature reports cytotoxic effects of zinc on the olfactory epithelium. Additional research suggests that divalent cations (such as zinc) can block ion channels that facilitate the transduction of odors into electrical signals on the olfactory epithelium. The purpose of the current study was 2-fold: to confirm whether zinc gluconate causes anosmia and to reveal whether any other divalent cationic compounds produce a similar effect. Groups of mice underwent a buried food-pellet test to gauge olfactory function and then were nasally irrigated with 1 of 3 divalent cationic compounds. When tested after treatment, mice irrigated with zinc gluconate and copper gluconate experienced a marked increase in food-finding time, indicating that they had lost their ability to smell a hidden food source. Control mice irrigated with saline had a significantly lower increase in times. These results confirm that zinc gluconate can cause anosmia and reveal that multiple divalent cations can negatively affect olfaction.